THE EFFECT OF PROJECT-BASED LEARNING MODEL ON IMPROVING STUDENTS' RELIGIOUS CHARACTER - Iman, Ahmad Nailul; Subakri, Subakri; Indrianto, Nino (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to analyze the influence of a project-based learning model on improving students’ religious character. Although this learning model is known to effectively encourage active student engagement, its impact on the religious dimension has rarely been examined. The research employed a quantitative method with a quasi-experimental approach. The sample consisted of 60 junior high school students divided into experimental and control groups. Data were collected using a religious character questionnaire covering dimensions of worship obedience, noble character, and tolerance. The results indicate a significant increase in religious character among students who learned using the project-based model compared to those who received conventional methods. This finding reflects the effectiveness of the method in helping students understand and internalize religious values. The collaborative factor in carrying out projects served as a key element supporting these results. Activities such as group discussions and peer evaluations encouraged students to share positive values. This study provides practical recommendations for teachers to implement project-based approaches to strengthen students’ character. However, the study is limited by its sample scope, which was confined to a single school. For broader generalization of the findings, further research encompassing a wider range of settings is needed. Overall, these results show that project-based learning is an effective approach for shaping students’ religious character.